2017
DOI: 10.1177/0897190017747424
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Academic Detailing Approach to Decrease Inappropriate Medication Prescribing by Physician Residents for Older Veterans Treated in the Emergency Department

Abstract: Academic detailing led by a physician-pharmacist pair resulted in improved confidence in physician residents' ability to prescribe safely in an older adult ED population and was associated with a statistically significant decrease in PIM rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…For example, VA providers in the emergency department who were paired with academic detailers reduced the rate of potentially inappropriate medications for older adults. 12 This study demonstrated the ability of academic detailing to adapt within a dynamic, face-paced practice environment such as emergency medical care. 12 Moreover, academic detailers are experienced practitioners with strong interposal skills and a deep understanding of clinical decision-making and are able to effectively engage a multitude of health care disciplines, thus expanding the potential for meaningful impact.…”
Section: Current Statementioning
confidence: 84%
See 1 more Smart Citation
“…For example, VA providers in the emergency department who were paired with academic detailers reduced the rate of potentially inappropriate medications for older adults. 12 This study demonstrated the ability of academic detailing to adapt within a dynamic, face-paced practice environment such as emergency medical care. 12 Moreover, academic detailers are experienced practitioners with strong interposal skills and a deep understanding of clinical decision-making and are able to effectively engage a multitude of health care disciplines, thus expanding the potential for meaningful impact.…”
Section: Current Statementioning
confidence: 84%
“… 8 In addition, as part of its mission to improve health care access, the VA Pharmacy Benefits Management (PBM) Service developed a virtual academic detailing (e-Detailing) model to improve the dissemination of critical health care information to providers in a timely fashion. 10 , 11 , 12 , 9 This commentary will highlight the opportunities for leveraging academic detailing during a pandemic to deliver timely resources to frontline providers. We use the VA academic detailing program as a model for other large, integrated health care systems, but we believe that these opportunities could be adapted for other systems.…”
mentioning
confidence: 99%
“…38 Previous research found that PCPs have either not heard of or used the Beers Criteria when prescribing medications for older adults. 39,40 One barrier to appropriate prescribing in older adults is a lack of formal education on older adult prescribing. 40 The Beers Criteria is an important resource for NPs that emphasizes the benefit of limiting inappropriate medication prescribing in older adults and aims to reduce polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…An approach such as home care is strongly recommended by the World Health Organization for various countries with community-based service models, especially in developing countries [21,22]. Academic detailing or case conferences have been carried out in various countries as part of primary care [3,4,13,23,24]. Because the approaches discussed in this review are universal, they can be extended to developing countries in the context of existing services.…”
Section: Training Needs Of Pharmacistsmentioning
confidence: 99%
“…Canada, the United States, the United Kingdom, and Ireland have developed academic detailing as a form of education from pharmacists for doctors in the context of optimizing drug services for the elderly. In these countries, education through academic detailing provides promising results for improving medication prescriptions from doctors for the elderly [2][3][4]. Educational activities that are needed and can be done by pharmacists in other forms include the provision of information on contraindications and drug interactions for the elderly seeking non-prescription drugs in pharmacies [5].…”
Section: Introductionmentioning
confidence: 99%